The Experience Economy - B. Joseph Pine II; James H. Gilmore (USA Harvard Business School Press, 2011)
In 1999, Joseph Pine and James Gilmore offered this idea to readers as a new way to think about connecting with customers and securing their loyalty. As a result, their book The Experience Economy is now a classic, embraced by readers and companies worldwide and read in more than a dozen languages. And though the world has changed in many ways since then, the way to a customer's heart has not. In fact, the idea of staging experiences to leave a memorable-and lucrative-impression is now more relevant than ever. With an ongoing torrent of brands attacking consumers from all sides, how do you make yours stand out? Welcome to the new Experience Economy. With this fully updated edition of the book, Pine and Gilmore make an even stronger case that experience is the missing link between a company and its potential audience. It offers new rich examples-including the U.S. Army, Heineken Experience, Autostadt, Vinopolis, American Girl Place, and others-to show fresh approaches to scripting and staging compelling experiences, while staying true to the very real economic conditions of the day.
Keywords: Product management; Marketing; Diversification in industry; Customer services; Nonfiction; Business; Economics; Design; Entrepreneurship; Management; Communication; Sociology; Cultural; HRM: Contemporary Issues (HRM2074-N ); Global Citizenship (BIN1064-N)